Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1038/sj.onc.1201830
|View full text |Cite
|
Sign up to set email alerts
|

p27Kip1: a key mediator of retinoic acid induced growth arrest in the SMS–KCNR human neuroblastoma cell line

Abstract: Retinoic acid (RA) treatment of SMS ± KCNR neuroblastoma (NB) cells leads to G1 growth arrest and neuronal di erentiation. To investigate the molecular mechanisms by which RA alters cell growth, we analysed the expression and activity of components of the cell cycle machinery after culture in RA. Within 2 days of RA treatment and prior to the arrest of NB cells in the G1 phase of the cell cycle, there is a complete downregulation of G1 cyclin/Cdk activities. Protein levels for the G1 cyclin/Cdks were essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 26 publications
3
57
0
Order By: Relevance
“…The cyclin E-dependent kinase activities in cultures treated with RA were reduced to less than 20% of the control while cyclin D-dependent kinase activity was reduced to 50% of the control (Figure 1e). Consistent with our previous results 6 the increases in p27 steady-state levels stimulated with RA were accompanied by increases in p27 bound to cyclin E (Figure 1f). These results raise the possibility that decreases in N-myc and Cdk6 and an increase in p27 play important roles in RA induced arrest of NB cell growth.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…The cyclin E-dependent kinase activities in cultures treated with RA were reduced to less than 20% of the control while cyclin D-dependent kinase activity was reduced to 50% of the control (Figure 1e). Consistent with our previous results 6 the increases in p27 steady-state levels stimulated with RA were accompanied by increases in p27 bound to cyclin E (Figure 1f). These results raise the possibility that decreases in N-myc and Cdk6 and an increase in p27 play important roles in RA induced arrest of NB cell growth.…”
Section: Resultssupporting
confidence: 81%
“…6 In this study, we found that there was a five-fold decrease in the levels of Cdk6 protein in KCNR cells treated for 72 h with RA ( Figure 1c). The steadystate levels of Cdk6 were decreased in time-dependent manner in RA-treated KCNR cells (data not shown).…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations